Pandemic Effect in Noncommunicable Disease Follow-up (Turkey Health Literacy Journal, 2021)
The first five diseases that make up the disease burden in the first quarter of the 21st century; cardiovascular diseases,cancers, mental illnesses, chronic airway diseases and diabetes. World Healthcare, which emerged in Wuhan city and spread rapidly all over the world, as of March 12, 2020. Covid 19, declared by its organization as a pandemic, is a serious threat to all people physically, spiritually and socially. Noncommunicable diseases (NCD), during the New Coronavirus Disease (COVID-19) It has become a situation that requires much attention. Numerous articles have been written opinions and has been shared on this subject. In this study, measures for the prevention and control of noncommunicable diseases are tried to draw attention to the importance of the period.